Assessment of CYP3A‐mediated drug–drug interaction potential for victim drugs using an in vivo rat model. (14th August 2013) - Rioux, Nathalie; Bellavance, Edith; Bourg, Serge; Garneau, Michel; Ribadeneira, Maria D.; Duan, Jianmin
ABSTRACT The present study aims to determine if an in vivo rat model of drug–drug interaction (DDI) could be useful to discriminate a sensitive (buspirone) from a 'non‐sensitive' (verapamil) CYP3A substrate, using ketoconazole and ritonavir as perpetrator drugs. Prior to in vivo studies, ketoconazole and ritonavir were shown to inhibit midazolam hydroxylation with IC50 values of 350 ± 60 nm and 11 ± 3 nm, respectively, in rat liver microsomes (RLM). Buspirone and verapamil were also shown to be substrates of recombinant rat CYP3A1/3A2. In the rat model, the mean plasma AUC0‐inf of buspirone (10 mg/kg, p.o.) was increased by 7.4‐fold and 12.8‐fold after co‐administration with ketoconazole and ritonavir (20 mg/kg, p.o.), respectively. The mean plasma AUC0‐inf of verapamil (10 mg/kg, p.o.) was increased by 3.0‐fold and 4.8‐fold after co‐administration with ketoconazole and ritonavir (20 mg/kg, p.o.), respectively. Thus, the rat DDI model correctly identified buspirone as a sensitive CYP3A substrate (>5‐fold AUC change) in contrast to verapamil. In addition, for both victim drugs, the extent of DDI when co‐administered was greater with ritonavir compared with ketoconazole, in line with their in vitro CYP3A inhibition potency in RLM. In conclusion, our study extended the rat DDI model applicability to two additional victim/perpetrator pairs. In addition, we suggest that use of this model would increase our confidence in estimation of the DDI potential for victim drugs in early discovery. Copyright © 2013 John Wiley & Sons, Ltd.